Patient and rheumatologist perspectives on glucocorticoids: an exercise to improve the implementation of the European League Against Rheumatism (EULAR) recommendations on the management of systemic glucocorticoid therapy in rheumatic diseases. Issue 6 (17th September 2009) - van der Goes, M C; Jacobs, J W G; Boers, M; Andrews, T; Blom-Bakkers, M A M; Buttgereit, F; Caeyers, N; Choy, E H; Cutolo, M; Da Silva, J A P; Guillevin, L; Holland, M; et al.
Abstract : Objective: To explore perspectives among patients and rheumatologists on glucocorticoid (GC) therapy and European League Against Rheumatism (EULAR) recommendations on the management of systemic GC therapy in order to enhance implementation of the recommendations. Methods: Rheumatologists (from eight countries) and patients (from five countries) acquainted with GCs participated in separate meetings, during which positive and negative aspects of GC therapy were discussed and possible adverse events (AEs) were ranked for importance; in addition participants were asked to evaluate the published EULAR recommendations. The reports from these meetings and themes related to implementation of the recommendations were discussed during an international forum of the experts who had formulated the recommendations and patient participants. Results: In all, 140 patients (78% women; mean age 53 years; 61% patients with rheumatoid arthritis) and 110 rheumatologists (mean work experience 15 years) participated in the meetings. Osteoporosis, diabetes and cardiovascular diseases were ranked among the five most worrisome AEs by patients and rheumatologists. In both groups, there was agreement with most of the recommendations; the recommendations on GC information cards and GC use during pregnancy scored lowest. Ideas to improve implementation of the recommendations and a research agenda were generated. Conclusion: The patient and rheumatologist views on GCs corresponded to a large extent, reflected by concerns in both groups about osteoporosis, diabetes and cardiovascular diseases. Specific problems with the EULAR recommendations were identified and addressed to improve their implementation. This exercise shows that patient and rheumatologist perspectives should be included early in the process of formulating recommendations.